Harnessing CRISPR/Cas9 system to engineer disease resistance in solanaceous crops: current progress and future prospects - Ahmed, Shiuli; Wan Azizan, Wan Aina Sakeenah; Nazri, Farahziatul Roshidah; Md Hatta, Muhammad Asyraf (Czech Academy of Agricultural Sciences, 2025)
Crops belonging to the Solanaceae family, including potato, tomato, pepper, and tobacco possess considerable economic importance worldwide. However, their production is continuously under threat from plant pathogens. Farmers typically rely on resistant cultivars carrying one or several disease resistance (R) genes introduced through conventional breeding. Over time, a competitive host-pathogen coevolution can lead to major resistance breakdown. Genome editing is a significant research tool and avenue for the genetic improvement of crop species, as it enables the precise introduction of targeted genetic changes. This technology has been successfully used in various food crops, including those belonging to the Solanaceae family. The advent of the CRISPR/Cas9 genome editing system allows the rapid knockout of desirable genes. Plant pathogens often exploit host genes known as susceptibility (S) genes to facilitate their proliferation. Inactivation of these S genes may reduce the pathogen’s ability to infect plants and confer durable and broad-spectrum resistance. This review provides an overview of the current application of CRISPR/Cas9 to disrupt the S genes for the development of disease-resistant solanaceous crops. The technological limitations and potential strategies for overcoming these challenges are discussed.